Neuro-glial mechanisms underlying sex-based resilience to cardiorespiratory dysfunction in heart failure - Ortiz-Cisternas, F (PORTLAND PRESS LTD, 2026)
Cardiorespiratory disorders, such as sympathoexcitation and disordered breathing, are main hallmarks of chronic heart failure (CHF) associated with high morbidity and mortality. We recently reported that rostral ventrolateral medulla (RVLM) catecholaminergic (C1) neurons are hyperactive in rats with CHF, contributing to cardiorespiratory distress. Notably, CHF without reductions in ejection fraction is more frequent in women than in men, but detailed sex differences in cardiorespiratory pathophysiology, as well as the existence of a sex-dependent neurophysiological remodeling within the RVLM, remain unclear. Therefore, we aimed to characterize sex differences in cardiac, autonomic/respiratory function, RVLM C1 neuron, and glial cell activation, followed by experimentally induced volume overload CHF (with preserved ejection fraction) in adult Sprague-Dawley rats. At week 8 post-CHF induction, male CHF rats showed similar to 2.5-fold increased left ventricular dilation, while female CHF rats exhibited only similar to 1-fold increase. Unlike the females, both cardiac systolic (end-systolic pressure-volume relationship) and diastolic function (end-diastolic pressure-volume relationship) were depressed in male CHF rats. Indeed, cardiomyocyte calcium handling was impaired only in CHF male rats. Cardiac arrhythmogenesis, sympathoexcitation, and disordered breathing were all significant in CHF male rats but were nearly absent in female rats. Consequently, we found that RVLM C1 neurons were not chronically active in female CHF rats compared with male CHF rats. In addition, we found that male CHF rats showed clear signs of astrocyte reactivity within the RVLM region that results in shifts towards higher astrocyte complexity. The latter was not present in female medullary astrocytes despite showing ventricular hypertrophy. Our results showed that gonadally intact female rats are somehow protected compared with intact male rats from RVLM astrocytic remodeling and chronic C1 neuronal activation following volume overload CHF, being the outcome a less severe cardiorespiratory pathology associated with the CHF phenotype.